Flow and its Relationship to Happiness Among Students of Law and Fine Arts Faculties at Damascus University - Alrobaie, Souad Yassin (Journal of Educational and Psychological Sciences, 2021)
The aim of current research is to study the relationship between psychological flow and happiness among a sample of Damascus University students (Faculties of Law and Fine Arts), in addition to know the differences in happiness and psychological flow due to variables (gender, faculty). The research used the descriptive correlative approach. the researcher used Jackson and Elkland flow questionnaire, and the Oxford happiness questionnaire prepared by Argyle and Hills; which applied to a sample of (300) students of the third year. The results showed that there is, statistically significant correlation between psychological flow and happiness (0.70) and there is statistically significant correlation between Happiness and each loss of self- consciousness, Merging of action and awareness, and sense of control with (0.63, 0.59, 0.47) respectively. Also the results showed there are no statistically significant differences in the psychological flow or in happiness among the members of the research sample due to the variable (sex) at level (0.05≥α). While there were statistically significant differences in the psychological flow among the members of sample due to the variable of (faculty), in favor of the students of Fine Arts faculty. According to the results of research, psychological flow explains about 70% of the total variance in happiness. Based on the results, the researcher presented a number of recommendations to improve the psychological growth and happiness among of the two colleges.
Keywords: Flow; Happiness; faculty of Law and Fine Arts; Damascus University